Optimizing the discharge process of a seasonal sorption storage system by means of design and control approach. (April 2023) - Crespo, Alicia; Frazzica, Andrea; Fernández, Cèsar; de Gracia, Álvaro
Abstract: Sorption thermal energy storage systems have higher energy densities and low long-term thermal losses compared to traditional energy storage technologies, which makes them very attractive for seasonal heat storage application. Although they have a lot of potential at material level, its operation and system implementation for residential application requires further study. The performance of a seasonal sorption thermal energy storage system strongly depends on the discharging process during the cold season. The present study analysed through numerical simulations different scenarios to enhance the thermal performance of a solar-driven seasonal water-based sorption storage, which supplied space heating and domestic hot water to a single-family house in a cold climate region. All studied scenarios were analysed under optimal control policy. The results indicated that the sorption storage could increase by 9 % its energy density if conservative and constant discharging temperature set points are considered, due to fewer interruptions during the discharge. The energy density of the sorption storage driven by solar energy was highly impacted by the weather conditions, and by the type and availability of low-temperature heat source. Indeed, the energy density of the sorption storage increased by 22 % using a water tank to assist the evaporator of the sorption storage, instead of a latent storage tank. The use of a dry-heater to assist the evaporator with environmental heat was not suitable for the climate studied due to the low hours of operation. The sorption storage system composed of 20 modules of LiCl-silica gel could obtain an energy density and a COP of 139 kWh/m 3 and 0.39, respectively, if a constant low-temperature heat source (i.e, geothermal or waste energy) was available. Highlights: Discharging efficiency of sorption TES highly impacted by the low-temperature heat source. The seasonal sorption TES submitted to transient weather conditions reached 106.4 kWh/m 3 . Ideal low-temperature heat source increased the sorption TES energy density by 23 %. Dry-heater not suitable as low-temperature heat source in Central Europe (Continental).